2003
DOI: 10.1037/0021-9010.88.1.160
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of emotional exhaustion to work attitudes, job performance, and organizational citizenship behaviors.

Abstract: The authors investigated the negative consequences of emotional exhaustion for individual employees and their employers. On the basis of social exchange theory, the authors proposed that emotional exhaustion would predict job performance, 2 classes of organizational citizenship behavior, and turnover intentions. In addition, the authors posited that the relationship between emotional exhaustion and effective work behaviors would be mediated by organizational commitment. With only a few exceptions, the results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

61
824
4
43

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,160 publications
(978 citation statements)
references
References 50 publications
61
824
4
43
Order By: Relevance
“…Their longitudinal study revealed nonsignificant relationships between depersonalization (a human-service-related form of disengagement) and performance (as rated by supervisors). Also, Cropanzano, Rupp, and Byrne (2003) found that emotional exhaustion was significantly negatively related to in-role performance as rated by supervisors, while the effect of emotional exhaustion on organizational citizenship behavior was fully mediated by organizational commitment (a measure that corresponds in a way to our disengagement dimension). Additionally, the finding that the two burnout dimensions were strongly related to (in-role or extra-role) performance while perceptions of work characteristics were unrelated to it has also been reported in the literature.…”
Section: Differential Effects Of Job Demands and Resourcesmentioning
confidence: 92%
“…Their longitudinal study revealed nonsignificant relationships between depersonalization (a human-service-related form of disengagement) and performance (as rated by supervisors). Also, Cropanzano, Rupp, and Byrne (2003) found that emotional exhaustion was significantly negatively related to in-role performance as rated by supervisors, while the effect of emotional exhaustion on organizational citizenship behavior was fully mediated by organizational commitment (a measure that corresponds in a way to our disengagement dimension). Additionally, the finding that the two burnout dimensions were strongly related to (in-role or extra-role) performance while perceptions of work characteristics were unrelated to it has also been reported in the literature.…”
Section: Differential Effects Of Job Demands and Resourcesmentioning
confidence: 92%
“…Indeed, social exchange theory suggests that employees who feel exhausted tend to make a negative assessment of the benefi ts received from the organization and that as a consequence, they may withdraw their effort as a response to the psychological costs incurred in fulfi lling their obligations (Cropanzano et al, 2003). Such a negative response would tend to be more salient among the least proactive employees.…”
Section: Emotional Exhaustionmentioning
confidence: 99%
“…Recent research has highlighted the important role of emotional exhaustion as a factor that hinders willingness to expand effort (Schaufeli & Taris, 2005) leading to suboptimal functioning (Leiter & Maslach, 2005). However, as specifi ed by Cropanzano, Rupp, and Byrne (2003), most studies have focused on the consequences of emotional exhaustion for individual workers, and have given relatively little attention to the organizationally relevant criteria of job performance and organizational citizenship behaviour (OCB). Given the paucity of research linking personality, emotional exhaustion, and performance in organizational settings (Witt, 2004), we investigated the moderating role of emotional exhaustion on the personality-individual performance relationship.…”
mentioning
confidence: 99%
“…Employees tend to form social exchange relationships with others so long as they feel they are receiving benefits out of that [9].…”
Section: Results -Theories Usedmentioning
confidence: 99%